The construction of social identities through narratives in the classroom - Carvajal Becerra, Ruth Villelva (Universidad Pedagógica y Tecnológica de Colombia, 2013)
One of the most important ideas in social sciences is perhaps the concept of identity and the way these identities emerge from people. This paper shows some preliminary results of a research project which is being carried out with students from a public institution in a small town. Through the students' narratives and semi-structured interviews they freely express their thoughts and opinions about specific situations reflecting their multiple identities and the way these social identities emerge from students' life experiences.